ANALYSIS OF TOURISM ATTRACTION, ACCESSIBILITY, AMENITIES, AND ANCILLARY SERVICES TOWARDS LOYALTY WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE IN BETAWI SETU BABAKAN JAKARTA - La Are, Robert (Emerging Markets : Business and Management Studies Journal, 2017)
The satisfaction of tourists is a desirable achievement in the tourism sector, especially in one tourist destination. Satisfaction also has an influence on the emergence of loyalty. This study was conducted from February ? June 2015 to examine the effect of factors affecting the sake of the visitors of Setu Babakan and its impact on loyalty. These factors consist of Tourism Attraction, Amenities, Accessibility and Ancillary Services. Primary data were collected through observation of questionnaires distributed to tourists visiting and were enjoying tourism products at Betawi Cultural Village Setu Babakan, Jakarta. Questionnaire collected 120 respondents who then analyzed using the method of Multiple Linear regression analysis. The test result of Attraction Attractions is 0.570 with beta coefficient value of 0.117. Accessibility of 0.370 with beta coefficient value of -0.160. Amenities of 0.001 with the value of beta coefficient of -0.633. and Ancillary Services of 0.336 with the value of beta coefficient of -0.107. thus the whole factor is declared no effect on visitor satisfaction. Test Result of Satisfaction Factor of 0.000 with beta coefficient value of 0.955. thus Satisfaction has a positive and significant influence on Travelers Loyalty